2003
DOI: 10.1021/jm030829z
|View full text |Cite
|
Sign up to set email alerts
|

Soft Antimicrobial Agents:  Synthesis and Activity of Labile Environmentally Friendly Long Chain Quaternary Ammonium Compounds

Abstract: A series of soft quaternary ammonium antimicrobial agents, which are analogues to currently used quaternary ammonium preservatives such as cetyl pyridinium chloride and benzalkonium chloride, were synthesized. These soft analogues consist of long alkyl chain connected to a polar headgroup via chemically labile spacer group. They are characterized by facile nonenzymatic and enzymatic degradation to form their original nontoxic building blocks. However, their chemical stability has to be adequate in order for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
128
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(134 citation statements)
references
References 18 publications
5
128
1
Order By: Relevance
“…Three sections of data were collected via literature searches (1) a model building set, (2) a validation set, and (3) a prediction set of compounds [27][28][29]. The model building set was based on known QACs with data on the MIC of these compounds against E. coli.…”
Section: Data Collectionmentioning
confidence: 99%
“…Three sections of data were collected via literature searches (1) a model building set, (2) a validation set, and (3) a prediction set of compounds [27][28][29]. The model building set was based on known QACs with data on the MIC of these compounds against E. coli.…”
Section: Data Collectionmentioning
confidence: 99%
“…Quaternary ammonium compounds are actively prevented the growth bacterial growth against both Gram-positive and Gram-negative bacteria, as well as against other pathogenic species of fungi and protozoa [1]. It has been found that quarternary phosphonium salts also showed beneficial antibacterial activity [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Quaternary ammonium compounds are actively prevented the growth bacterial growth against both Gram-positive and Gram-negative bacteria, as well as against other pathogenic species of fungi and protozoa [1]. It has been found that quarternary phosphonium salts also showed beneficial antibacterial activity [2,3].Microbial protection is mainly dependent on long alkyl chains which are attached with the phosphonium salts. These can be enhanced strongly by the molecular structure, correlation between antimicrobial activity and molecular structure [4].…”
mentioning
confidence: 99%
“…Therefore, there is a need to develop more QUATS with antimicrobial activities. Quaternary ammonium compounds, in general, have toxic effects toward mammalian cells [9]. In humans and animals they are considered too toxic for systemic applications, but acceptable for topical applications.…”
Section: Introductionmentioning
confidence: 99%